Morphologic Characterisation of 1693 Cholecystecomy Specimens- A Study from Tertiary Care Center in Northern India - Savita Agarwal; Pinki Pandey; Megha Ralli; Ranjan Agarwal; Priyanka Saxena (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Cholecystectomies are most common surgical specimens sent in pathology laboratories. Most common histologically identified lesion of gallbladder is chronic cholecystitis which on most occasions is associated with cholelithiasis. It is most common indication for cholecystectomy and also associated with gallbladder carcinomas. Aim: The aim of the present was to study the morphological spectrum of gallstone disease and correlation of cholelithiasis with benign and malignant lesions. Materials and Methods: A retrospective study was carried out from January 2012 to June 2016. A total of 1693 specimens were assessed for size of gallbladder, serosa, wall thickness, mucosa, presence/absence of stones, their number, and type along with any mass lesions. Microscopic features assessed included inflammation, cholesterolosis, granulomas, metaplasia, calcification, dysplasia, benign and malignant neoplasms. Results: Maximum numbers of cases were between 31 to 40 years with female preponderance. Chronic cholecystitis was the most common lesion seen in 1170 (69.1%) cases. Associated calculi was present in 1625 cases, mixed and cholesterol type accounting for 1050 (64.6%) and 382 (23.51%) respectively based on morphological appearance. Amongst 439 cases showing metaplasia, antral type metaplasia was most common followed by intestinal metaplasia. Most frequent stromal change was cholesterolosis. Dysplasia was seen in 15 (0.88%) cases and malignancy in 16 cases. Conclusion: Incidental detection of gallbladder malignancy on microscopic examination is the most significant information for the surgeon as well as for the patient and this fact emphasises the importance of subjecting each gallbladder specimen for histopathological examination.